IMPLEMENTASI ENTERPRISE RESOURCE PLANNING BERBASIS OPEN SOURCE PADA USAHA SETIA MOTOR TARUTUNG - Siagian, Wesly Mailander; Sihite, Yeremi Febrian (Universitas Budi Luhur, 2024)
Utilization of technology is one of the steps that can be taken by MSMEs to compete with other MSMEs. Enterprise Resource Planning (ERP) is one of the information technologies that can be used by MSMEs. Setia Motor Tarutung is one of the MSMEs in needed implementation of the ERP to help integrate data and optimize currently business processes. This study aims to configure and conduct testing the ERP system with the Dolibarr application that can meet the business process needs of MSME Setia Motor Tarutung. The business process modeling will provide information regarding the current needs of MSME Setia Motor Tarutung. Thus, it is possible to modify an open source-based ERP system using the Dolibarr application and produce an ERP system that is able to meet the needed for current. The Business Process Modeling Notation (BPMN) method is used to identify the business processes of MSME Setia Motor Tarutung. Testing of the configured ERP system is carried out using the Black-Box Testing method. From the research conducted, it is found that business process modeling with the BPMN method has a major influence on the success of ERP implementation. From the results of the analysis, design and implementation, it was found that the basic Dolibarr modules and features were able to meet the needs of MSME business processes. The system test results show that all functions of the ERP system that have been configured can be used by owners properly and also meet the need of MSME Setia Motor Tarutung.